EKSPLOITASI WANITA DALAM PERSPEKTIF KAPITALIS - M.Hum, Syamsudin, (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2006)
In globalization era with its free market, to run a business successfully is very hard. Life is very competitive. And a business man, as the owner of the capital, will do everything for the success of his business. Employing women in many sectors of businesses can be a fruitful way. In this case, women have been exploited fully to follow what the business man wants. But they, the women, canâ€™t refuse it. Clearly, capitalism has created two classes in society: the capitalist group (capital owner) and the workerÂ group (non capital owner). basically exploitation of women in various of businesses is only one of the ways done by the capitalist to show individualism, to win competition, and to get as many benefits as possible in business.Â Above all, exploiting women is just one of the ways taken by the capitalist to survive in this competitive-free market. And as far as the capitalist still hold the economic system of the world, women exploitation will never end.